Fototriangulação com parâmetros adicionais para câmaras digitais: Uma avaliação experimental - Da Silva Ruy, Roberto [UNESP]; Tommaselli, Antonio Maria Garcia [UNESP]; Galo, Mauricio [UNESP]; Hasegawa, Julio Kiyoshi [UNESP]; Menossi, Ricardo Cesar (My University, 2008)
Considering the growing use of digital cameras in Photogrammetric projects, especially in aerial survey, this paper presents tests and analyses of bundle block adjustment with additional parameters, using different mathematical models, and blocks of images acquired by the SAAPI digital acquisition system. Three blocks of images were processed by the LPS (Leica Photogrammetry Suite) software, in which five groups of additional parameters (AP) can be used: Bauer, Jacobsen, Ebner, Brown and Lens distortion. These AP's models were employed in the bundle block adjustment, and the results were analyzed based on the accuracy of the checking points and on the changes in these additional parameters. The obtained results showed that the Lens Distortion model allowed the best results.
Bundle block adjustment with additional parameters for digital camera: An experimental assessment
Keywords: Bundle block adjustment with additional parameters; Digital cameras